2019
DOI: 10.3389/fnins.2019.00146
|View full text |Cite
|
Sign up to set email alerts
|

Cholinergic Deficit Induced by Central Administration of 192IgG-Saporin Is Associated With Activation of Microglia and Cell Loss in the Dorsal Hippocampus of Rats

Abstract: Alzheimer’s disease (AD) is associated with degeneration of cholinergic neurons in the basal forebrain. Administration of the immunotoxin 192IgG-saporin to rats, an animal model of AD, leads to degeneration of cholinergic neurons in the medial septal area. In the present study, cholinergic cell death was induced by intracerebroventricular administration of 192IgG-saporin. One and a half months after injection, we studied the histopathology of the hippocampus and the responses of microglia and astrocytes using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 45 publications
2
13
0
Order By: Relevance
“…These effects were not linked to a direct action of the immunotoxin because of the lack of the nerve growth factor receptors in the hippocampus. Therefore, the selective death of cholinergic neurons in the medial septal area and diagonal band can be considered the major factor leading to the specific vulnerability of Ammon's Horn neurons, both in rats [99] and in mice (present data). Interestingly, some AD cases are associated with a neuronal loss in specific Ammon's Horn sub-fields (e.g., CA3; [100,101]).…”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation
“…These effects were not linked to a direct action of the immunotoxin because of the lack of the nerve growth factor receptors in the hippocampus. Therefore, the selective death of cholinergic neurons in the medial septal area and diagonal band can be considered the major factor leading to the specific vulnerability of Ammon's Horn neurons, both in rats [99] and in mice (present data). Interestingly, some AD cases are associated with a neuronal loss in specific Ammon's Horn sub-fields (e.g., CA3; [100,101]).…”
Section: Discussionmentioning
confidence: 58%
“…Cholinergic depletion per se reduced hippocampal volume (specifically of the whole hippocampus and Ammon's Horn, but not of DG) and increased hippocampal astrogliosis in agreement with findings in rats and AD patients. In fact, recently Dobryakova et al [99] found that 192 IgG-saporin lesions in rats resulted in a significant CA3 neuronal loss accompanied by microglial proliferation, dense gliosis, and strong activation of astrocytes in the DG and white matter. These effects were not linked to a direct action of the immunotoxin because of the lack of the nerve growth factor receptors in the hippocampus.…”
Section: Discussionmentioning
confidence: 99%
“…DH appears to be primarily responsible for the cognitive functions of the hippocampus (Moser & Moser, 1998;Sahay & Hen, 2007;Barkus et al, 2010;Fanselow & Dong, 2010), which is consistent with our finding that that genes associated with learning and memory were only impacted in DH. Our findings also add to evidence suggesting that DH is more vulnerable to neuroinflammation and other pathology than VH (Fuster-Matanzo et al, 2011;Stouffer et al, 2015;Dobryakova et al, 2017;Dobryakova et al, 2019;Tournier et al, 2019).…”
Section: Discussionsupporting
confidence: 76%
“…The authors also found that cortical noradrenergic deficit was associated with compromised function of blood-brain barrier and remodeling of vessel structure, which resembled pathological stenosis. These data as well as our data that cholinergic deficit induced by 192IgG-saporin may lead to altered expression of vascular transport proteins [124] point to an important role that may be played by disturbed vascular function in AD pathogenesis.…”
Section: Alzheimer's Diseasesupporting
confidence: 75%
“…Recently, we have applied a transcriptomic approach to study whether 192IgG-saporin induces neuroinflammatory consequences in the hippocampus. Administration of immunotoxin into the cerebral ventricles resulted in moderate impairments of cognitive functions which were associated not only with loss of cholinergic neurons in the medial septum, but also with loss of neurons in the CA3 field of the hippocampus [124,126]. Microglia proliferation was observed in the dorsal hippocampus and in the white matter.…”
Section: Alzheimer's Diseasementioning
confidence: 99%